Microbial pathogenesis and the evasion strategies from the legume plant protective immunity. Issue 1 (11th October 2022) - Noor, Rashed
Abstract: Plants are stringent sources for the global food supply, and among them, legumes are considered to be the special ones since they have the specific capability to develop a symbiotic relationship with certain soil microorganisms (i.e., the rhizobial community) which deliberately fix the atmospheric nitrogen that is required for the further cellular synthesis. Biological nitrogen fixation (BNF) by the legume plants is essential for viable agricultural production and to decrease the use of synthetic nitrogen fertilizer in the agricultural fields. However, being the indigenous soil habitants, almost all plants are constantly encountering soil bacteria, viruses, fungi, nematodes, and so on, which may instigate an array of plant diseases conferring the global food security risk. Assimilation of plant nutrients is largely driven by the specific symbiotic interaction between rhizobial species and the leguminous plant roots through the formation of root nodules. Hence, in order to improve the crop yield and to ensure a sustainable supply of plant proteins and other nutrients, the protective immunity of the legume plants against the plant pathogens needs to be understood well because legumes comprise the maximum portion of all plants for serving as the human food and livestock feed. Present review emphasized on the bacterial pathogens and the virulent genes that are detrimental to plants including legumes. The evasion strategy of these harmful microorganisms from the plants' protective immunity is also discussed.